Revenue Estimation of Pit Seam 14 Quarter Mine Block Sequence Design Based on Coal Reference Price Prediction at PT Alam Jaya Pratama, East Kalimantan Province - Aryanti Virtanti Anas; Rahmat Hidayat; Rizki Amalia; Muhammad Ramli; Nirmana Fiqra Qaidahiyani; Yoga Apri Disetia (Center of Techonolgy (COT), Engineering Faculty, Hasanuddin University, 2020)
Seam 14 is one of coal prospects owned by PT Alamjaya Bara Pratama (PT ABP) with an estimated coal resources of ±4,022,458.63 tons which is will be produced in 2020 so that required a pit and mine sequence design used as a guideline in carrying out coal production activities. On the other hand, the uncertainty of coal prices caused the mine sequence design to be evaluated within a certain time as the coal reference price (HBA) was altered and company’s production target. The model equation of coal reference price prediction in 2020 was carried out by using multiple linear regression method. Based on that model, prediction of coal reference price was obtained in CW 1 = 80.21, CW 2 = 81.47 and CW 3 = 82.50. The Pit 14 was designed with the consideration of company's geotechnical recommendation which is can be achieved on the conditions of stripping ratio (SR) of 6 and 7. The mine sequence was designed base on the evaluation of coal production in 2019 (CW 1 = SR > 3, CW 2 = 3 ≤ SR ≤ 6 and CW 3 = SR > 6). The calculation results of estimated revenue of Pit 14 with SR = 6 is CW 1 = US40,131,297.12; CW 2 = US36,431,457.31; and CW 3 = US19,601,965.40. Estimated revenue of Pit 14 with SR = 7 is CW 1 = US41,821,080.50; CW 2 = US39,204,128.39; and CW 3 = US31,715,767.60.